2015
DOI: 10.1186/s12875-015-0387-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk of exacerbation in chronic obstructive pulmonary disease: a primary care retrospective cohort study

Abstract: BackgroundThe risk of exacerbation in chronic obstructive pulmonary disease (COPD) depends on the severity of disease and other less well known factors. Predictive models of exacerbation are more accurate than the forced expiratory volume in one second (FEV1). The objective was to design a model that predicts the risk of exacerbation in COPD.MethodsRetrospective cohort study with data from the electronic medical records of patients diagnosed with COPD in the province of Lleida (Spain). A total of 2501 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 38 publications
2
19
0
2
Order By: Relevance
“…The frequent exacerbator is an interesting phenotype, as exacerbations are in general linked to infections and the susceptibility for infections increases with age [70,71]. Moreover, age is a risk factor for COPD exacerbations [72] and hospital admissions for acute exacerbations of COPD [73].…”
Section: Lung Ageing and Copd Phenotypesmentioning
confidence: 99%
“…The frequent exacerbator is an interesting phenotype, as exacerbations are in general linked to infections and the susceptibility for infections increases with age [70,71]. Moreover, age is a risk factor for COPD exacerbations [72] and hospital admissions for acute exacerbations of COPD [73].…”
Section: Lung Ageing and Copd Phenotypesmentioning
confidence: 99%
“…A Spanish study that included 2501 patients over a 3‐year period, showed that older patients had at least one episode of exacerbation during the follow‐up period. In their study an over 68 age was the second predictor factor of future risk of exacerbations in the history of exacerbations …”
Section: Age Of Patients and Body Mass Indexmentioning
confidence: 92%
“…Several studies showed that older age and low body mass index (BMI) were associated with higher rate of acute exacerbation episodes . A large study carried out in Scotland, which included 3342 patients with COPD that had been followed for a long period of time (median 1.9 years) showed that the increasing age and a low BMI were associated with poor outcome .…”
Section: Age Of Patients and Body Mass Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the association of a range of variables with frequency of different COPD exacerbations (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%